Pemanfaatan Limbah Ternak sebagai Media Pembuatan Bioinsektisida Berbahan Aktif Bacillus thuringiensis dalam Mendukung Pengendalian Hama Terpadu: Utilization of Livestock Waste as a Medium Producing Bacillus thuringiensis-Bioinsecticides Containing in Supporting Integrated Pest Control - Yulia Pujiastuti; Arsi Arsi; Suparman Suparman; Abu Umayah; Bambang Gunawan; Weri Herlin (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Livestock waste becomes a problem and disturbs the community environment. In addition to the odor generated, it causes an unclean environment. Livestock waste is a problem for the people of Jungkal Village, Pampangan District, Ogan Komering Ilir Regency, South Sumatra. Good environmental management must be a priority. Therefore, livestock waste must be utilized to create a healthy environment. The purpose of this activity was to explain the use of livestock waste as a medium to produce bio-insecticides made from the active Bacillus thuringiensis bacteria. The target community was a farmer group in Jungkal Village. Activities were carried out in two ways, namely socialization activities and practical activities to produce bio-insecticide with active B. thuringiensis. Preliminary data showed that farmers were aware that livestock waste causes discomfort. Handling both liquid and solid waste has yielded little results because, so far, farmers have only gotten rid of this waste without using it as a helpful product. After the community service activities were completed, 80% of the participants understood the benefit of livestock waste. With an intensive approach and assistance, farmer groups can receive new directions.